Prevalence of Plasmodium falciparum Infection Among Patients Attending Health Facilities in Northern Taraba State, Nigeria - Chibuzor Obiorah Sylvester; Allahnanan Emmanuel; Peace Christopher Njideka; Chukwuebuka Igboaka Duke (Darul Yasin Al Sys, 2025)
Plasmodium falciparum remains the primary cause of malaria-related mortality, particularly in sub-Saharan Africa, representing a significant global health challenge. This study aimed to assess the prevalence of P. falciparum infection among patients attending health facilities across the Northern Local Government Areas of Taraba State. Employing a prospective cross-sectional design, the study enrolled 1,500 participants who underwent testing for P. falciparum using Giemsa-stained blood film examination, Rapid Diagnostic Tests (RDT), and Polymerase Chain Reaction (PCR). Hematological parameters, including Packed Cell Volume (PCV), white blood cell counts, and erythrocyte sedimentation rate (ESR), along with biochemical markers such as albumin, bilirubin, and electrolyte levels, were also assessed. The results indicated that Jalingo had the highest prevalence at 25.4%, followed by Lau with 18.8%, which is lower than the 45% reported in the same local government area (Adiel et al., 2021). Zing exhibited the lowest prevalence at 16.6%, marking this study as the first reported malaria investigation in the Zing Local Government Area. Contrary to expectations, Jalingo, the state capital, showed a higher prevalence of malaria, suggesting factors such as socio-environmental lifestyles, rural-urban migration, artificial vector breeding sites, urban agriculture, and reduced immunity among urban dwellers may contribute to this trend. The overall prevalence of malaria across the three sites was 20.27%. These findings emphasize the need for comprehensive diagnostic strategies and advocate for the integration of adjunct tools into malaria treatment protocols to improve patient care and outcomes.